2020
DOI: 10.1111/jiec.13026
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability assessment of a novel micro solar thermal: Biomass heat and power plant in Morocco

Abstract: Novel renewable energy technologies in the Middle East and North Africa region can be developed through microgeneration systems aiming to supply local energy demands in a sustainable way. In this study, we carried out a sustainability assessment combining two reputable methodologies which have been applied to a facility comprising a hybrid solar/biomass micro‐cogeneration organic ranking cycle system located in Morocco. We first applied a multiregional input–output analysis where economic issues such as the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Resource depletion and human toxicity were not negligible due to the solar field. Similar results were obtained in Morocco [113]. One of the solutions to promote renewables would be to retrofit existing dams to generate electricity from hydro power.…”
Section: A Focus On Lca For Energysupporting
confidence: 77%
See 1 more Smart Citation
“…Resource depletion and human toxicity were not negligible due to the solar field. Similar results were obtained in Morocco [113]. One of the solutions to promote renewables would be to retrofit existing dams to generate electricity from hydro power.…”
Section: A Focus On Lca For Energysupporting
confidence: 77%
“…It can be observed that these eight countries account for two thirds of the total number of African LCA publications. This highlights the fact that currently only [111] Electric energy 1 kWh of produced electric energy Primary data/Gabi/Ecoinvent v3.1 CML2001 Morocco [112] Automotive headrest 1 headrest for automotive seating Primary data/Ecoinvent IMPACT 2002+ Morocco [113] hybrid solar/biomass micro-cogeneration 1 kWh of electricity Primary data/WIOD/EORA ILCD Morocco [114] Solar water heater Utilization during one year Primary data Other Morocco [115] Waste Water Treat effluent of one population equivalent for one day Primary data ReCiPe midpoint 2014 Mozambique [116] Jatropha oil 1 MJ of energy in the form of jatropha oil or fossil diesel Primary data/Existing literature Other Mozambique [117] Biomass power plant 1-GJ pellets delivered to a combined heat and power (CHP) plant…”
Section: Articless Published Per Yearmentioning
confidence: 99%